Implementation of The Carrier Model in Innovative and Interactive Training of Video Making - Indri Astuti; Aloysius Mering; Elva Nopianti; Darini Darini (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
The purpose of this community service activity (PKM) is to improve the pedagogic competence of teachers in using technology in learning through training activities for making innovative and interactive learning videos assisted by the PEDATI model. Participants in community service are elementary, middle, and high school/vocational school teachers. Activities are carried out online with the Google Meet application. The implementation of this training uses three methods: the presentation method with change management materials, the PEDATI learning model on online learning materials with games and quizzes. The demonstration method of participants being interactively involved in Quiz games in online learning, the installation process and tutorials for developing learning videos using Camtasia, and the practical method by assigning participants to make learning videos according to their fields. The results obtained from the training are the availability of applications for making learning videos, insight into the development of learning videos, and the outcomes of learning video products with the Camtasia application made by teachers based on needs analysis according to student characteristics, subjects, and media used by teachers in classroom learning.